2020
DOI: 10.4310/jdg/1583377215
|View full text |Cite
|
Sign up to set email alerts
|

On the entropy of closed hypersurfaces and singular self-shrinkers

Abstract: Self-shrinkers are the special solutions of mean curvature flow in R n+1 that evolve by shrinking homothetically; they serve as singularity models for the flow. The entropy of a hypersurface introduced by Colding-Minicozzi is a Lyapunov functional for the mean curvature flow, and is fundamental to their theory of generic mean curvature flow.In this paper we prove that a conjecture of Colding-Ilmanen-Minicozzi-White, namely that any closed hypersurface in R n+1 has entropy at least that of the round sphere, hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 19 publications
(53 reference statements)
0
32
0
Order By: Relevance
“…In [3], Bernstein-Wang showed that the round spheres S n uniquely minimize the entropy (modulo dilations and rigid motions) among closed hypersurfaces in R n+1 for 2 ≤ n ≤ 6, giving an affirmative answer to a conjecture made by Colding-Ilmanen-Minicozzi-White in [8]. Later, Zhu [25] extended the result to all higher dimensions. In [5], Bernstein-Wang further showed that, for n = 2, the round sphere is Hausdorff stable under small perturbations of entropy.…”
Section: Introductionmentioning
confidence: 89%
“…In [3], Bernstein-Wang showed that the round spheres S n uniquely minimize the entropy (modulo dilations and rigid motions) among closed hypersurfaces in R n+1 for 2 ≤ n ≤ 6, giving an affirmative answer to a conjecture made by Colding-Ilmanen-Minicozzi-White in [8]. Later, Zhu [25] extended the result to all higher dimensions. In [5], Bernstein-Wang further showed that, for n = 2, the round sphere is Hausdorff stable under small perturbations of entropy.…”
Section: Introductionmentioning
confidence: 89%
“…This verifies a conjecture of Colding-Ilmanen-Minicozzi-White [6, Conjecture 0.9] (cf. [16,24] for related interesting results). We further show, in [3,Corollary 1.3], that surfaces in R 3 of small entropy are topologically rigid.…”
Section: Introductionmentioning
confidence: 92%
“…As Colding and Minicozzi point out in [6], the entropy λ(Σ s ) does not necessarily depend smoothly on s; we are only interested though in when we can say it is continuous. We start by proving what one can interpret as a very weak version of Bernstein and Wang's results [3] (see also [21] for the extension to higher dimensions), where as a consequence of their work it was shown the entropy of a closed hypersurface is bounded below by the entropy of the round sphere: Proof: Suppose not. Then there exists a sequence Σ i ∈ Π C,D so that λ(Σ i ) < 1+ 1 i .…”
Section: Lipschitz Continuity Of Entropy In Certain Casesmentioning
confidence: 94%